MicroRNAs in CSF as prodromal biomarkers for Huntington disease in the PREDICT-HD study. (23rd January 2018) - Reed, Eric R.; Latourelle, Jeanne C.; Bockholt, Jeremy H.; Bregu, Joli; Smock, Justin; Paulsen, Jane S.; Myers, Richard H.
Abstract : Objective: To investigate the feasibility of microRNA (miRNA) levels in CSF as biomarkers for prodromal Huntington disease (HD). Methods: miRNA levels were measured in CSF from 60 PREDICT-HD study participants using the HTG protocol. Using a CAG–Age Product score, 30 prodromal HD participants were selected based on estimated probability of imminent clinical diagnosis of HD (i.e., low, medium, high; n = 10/group). For comparison, participants already diagnosed (n = 15) and healthy controls (n = 15) were also selected. Results: A total of 2, 081 miRNAs were detected and 6 were significantly increased in the prodromal HD gene expansion carriers vs controls at false discovery rate q < 0.05 (miR-520f-3p, miR-135b-3p, miR-4317, miR-3928-5p, miR-8082, miR-140-5p). Evaluating the miRNA levels in each of the HD risk categories, all 6 revealed a pattern of increasing abundance from control to low risk, and from low risk to medium risk, which then leveled off from the medium to high risk and HD diagnosed groups. Conclusions: This study reports miRNAs as CSF biomarkers of prodromal and diagnosed HD. Importantly, miRNAs were detected in the prodromal HD groups furthest from diagnosis where treatments are likely to be most consequential and meaningful. The identification of potential biomarkers in the disease prodrome may prove useful in evaluating treatments that may postpone disease onset. Clinicaltrials.gov identifier: NCT00051324.